2014
DOI: 10.1016/j.nbd.2014.06.012
|View full text |Cite
|
Sign up to set email alerts
|

A marked paucity of granule cells in the developing cerebellum of the Npc1−/− mouse is corrected by a single injection of hydroxypropyl-β-cyclodextrin

Abstract: In this study we show that postnatal development of cerebellar granule neurons (GNs) is defective in Npc1−/− mice. Compared to age-matched wild-type littermates, there is an accelerated disappearance of the external granule layer (EGL) in these mice. This is due to a premature exit from the cell cycle of GN precursors residing at the level of the EGL. As a consequence, the size of cerebellar lobules of these mice displays a 20%–25% reduction compared to that of age-matched wild-type mice. This size reduction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 59 publications
4
32
0
Order By: Relevance
“…In support of this, abnormal expression and localization of SHH and its receptor Patched has been shown in the cerebellum of Npc1 mutant mice at P14 as well as in NPC1 patient-derived fibroblasts [63,64]. These data along with other studies highlighting the importance of cholesterol for SHH function in the developing cerebellum suggest that important connections may exist between NPC1 and SHH signaling pathways [58,65,66].…”
Section: Discussionsupporting
confidence: 59%
“…In support of this, abnormal expression and localization of SHH and its receptor Patched has been shown in the cerebellum of Npc1 mutant mice at P14 as well as in NPC1 patient-derived fibroblasts [63,64]. These data along with other studies highlighting the importance of cholesterol for SHH function in the developing cerebellum suggest that important connections may exist between NPC1 and SHH signaling pathways [58,65,66].…”
Section: Discussionsupporting
confidence: 59%
“…The Sonic Hedgehog (SHH) Signaling pathway (Supplementary Materials Figure S7C), known to be critical for cerebellar patterning [67], is predicted to be increased in lobule X. Additionally, NPC1-specific abnormalities in SHH signaling have been described, leading to a reduction of ciliated cells in the Npc1 −/− mice mouse brain [68]. During development, mRNA levels of Shh are decreased in Npc1 −/− mice and likely results in defective proliferation of granule neurons within the cerebellum, as granule neuron proliferation is sustained by consistent levels of SHH [69]. Granule neuron function is important in the context of NPC1 and Purkinje neuron degeneration because they are the only excitatory neurons within the cerebellum and their parallel fibers within the molecular layer directly activate Purkinje neurons [70].…”
Section: Npc1-independent Expression Modulesmentioning
confidence: 99%
“…A randomized controlled study showed that miglustat, an inhibitor of glucosylceramide synthesis, improves saccadic eye movements, swallowing capacity, and ambulatory capacity [Patterson et al 2007]. Recently, 2-hydroxypropyl-beta-cyclodextrins (HPBCD) has gained attention as a promising candidate [Camargo et al 2001;Nusca et al 2014;Vite et al 2015]. HPBCD increases the solubility of poorly water-soluble compounds such as cholesterol [Vite et al 2015].…”
Section: Metabolic and Toxic Diseases Hypothyroidism Wernicke Encephmentioning
confidence: 99%